A Study on the CTC Method Grinding Machine in Black Tea Processing at PTPN IV Unit Kebun Sidamanik - Winforstein Naibaho; Ayub Januari Sidauruk; Tambos Agust Sianturi (Jurnal Ilmiah Multidisiplin Nusantara (JIMNU), 2025)
Black tea processing Is categorized into two methods: (1” Orthodox and (2) CTC (Crushing, Tearing, and Curling). These methods are implemented through hands-on activities at the company/factory based on theoretical knowledge, which is then applied in the form of field work practice (PKL). The conclusions drawn from the field work practice are as follows: The Sidamanik Plantation Is one of 24 tea plantations under the Sidamanik Plantation Unit of PTPN IV, located in Sidamanik ’istrict. The CTC black tea produced at the Sidamanik factory Is then shipped to the main factory for ’lending there, with the composition regulated by the technology department, as the CTC black tea from the Sidamanik factory does not yet have a s’les label. At the Sidamanik factory, grinding Is performed in two stages using a 15” Rotorvan” (RV) machine for the first grinding and a 36” Teaman CTC 4-Cut machine with four sets of sequential rollers for the second grinding. The Rotorvane’s capacity is 484,739.3533 kg of withered tea leav’s per hour, equivalent to 581,710.4923 ’g of fresh withred tea leaves per hour, and equivalent to ’21,810.1771 kg of dry tea per hour” The CTC plant’s capacity is 18,274.7704 kg of ground tea pe” hour, equivalent to a capacity of 21,930.6017 kg of fresh withered tea leaves per hour, and ”quiv’lent to a capacity of 4,592.2680 k” of dry tea per hour